(untitled) (Bangladesh Journal of Agricultural Research, 2023)
An experiment was conducted during rabi and kharif season of 2018 - 2019 and 2019-2020, respectively at Regional Agricultural Research Station (RARS), Cumilla to find out the suitable crop combination of leafy vegetables with brinjal for increasing productivity and economic return through intercropping system. Five treatments viz. Brinjal + Red amaranth (T1), Brinjal + Leaf amaranth (T2), Brinjal + Patshak (T3), Brinjal + Spinach (T4) and Sole crop of brinjal (T5) were used in rabi season. In kharif season all the treatments were same except T4 where Indian spinach was used with brinjal instead of spinach. Results showed that yield and yield contributing characters of brinjal did not differ significantly due to different intercropping systems. Yield of brinjal was comparatively low in intercropping but total productivity increased due to additional yield of leafy vegetables. Increase of total productivity in terms of brinjal equivalent yield (BEY) was 2.03 to 25.68% (Rabi) and 2.36 to 22.29% (Kharif) and in intercrop combination compared to sole crop. All the intercropping combinations showed higher brinjal equivalent yield (BEY), gross return and benefit cost ratio (BCR) over sole crop. Among the intercropping combinations, Brinjal + Spinach (rabi) and Brinjal + Indian spinach (kharif-1) was the most feasible and profitable in respect of BEY (48.94 and 27.62 t/ha, respectively), gross return (Tk. 1223400 and 1105000/ha, respectively), gross margin (Tk.908823 and 782487/ha, respectively) and benefit cost ratio (3.88 and 3.42, respectively). Bangladesh J. Agril. Res. 46(1): 89-97, March 2021